The most important thing : uncommon sense for the thoughtful investor - Marks, Howard, 1946- (Columbia Business School publishing., 2011)
"Informed by a lifetime of experience and study, The Most Important Thing explains the keys to successful investment and the pitfalls that can destroy capital or ruin a career. Utilizing passages from his memos to illustrate his ideas, Marks teaches by example, detailing the development of an investment philosophy that fully acknowledges the complexities of investing and the perils of the financial world. Brilliantly applying insight to today's volatile markets, Marks offers a volume that is part memoir, part creed, with a number of broad takeaways."--